Kemiskinan dalam Perspektif Sosiologi - Wardaya, Sulistya; Suprapti, Anni (JSW (Jurnal Sosiologi Walisongo), 2018)
This paper describes the social and cultural situation of Pematang Gubernur Village, Muara Bangka Hulu Sub-district, Bengkulu City. Formerly, this area belongs to Suku Lembak who lived in Tanjung Agung and Tanjung Jaya village. The population of Pematang Gubernur has increased along with the establishment of Bengkulu University housing and the relocation of government office of Bengkulu City to Muara Bangka Hulu Sub-district. Based on the sociological analysis, Suku Lembak becomes a minority group in their own territory and as a minority, they are no longer able to carry out their customs and traditions, in contrast, the migrants that have become majority group, in fact, can apply their traditions and rituals from their origin. This research found that the social structure of Pematang Gubernur Village is seeking its ideal format. The community of the village is diverse and live in different groups based on housing complex and kampong. This makes the community divided and trapped in the situation in which the interaction between groups is limited. This also makes the community of Padang Gubernur has a narrow perspective in understanding poverty by seeing it as merely a problem of success and failure in pursuing the career and business of their neighbors. They also have narrow self-orientation and non-competitive capacities.